KONSELING KELUARGA DALAM MEREDUKSI ANAK ADIKSI GAME ONLINE - Asna, Asna (Journal of Education Counseling, 2023)
Online games are games that are connected to the network and the internet, there are many features in online games that are increasingly interesting. Online games have grown rapidly and not only among children, but also adults and even parents. This is a special concern for parents who have children who often play online games, resulting in online game addiction in these children, the importance of family counseling to reduce online game addiction to children to solve problems that occur because the negative impact of online games on children is very worrying about the future of the child and must be done immediately on how to provide assistance and solutions. This study takes the subject of a family who has a child with an online game addiction condition and what are the impacts of the child. The purpose of this study is to find out about online games and what kinds of online games are.